Comprehensive assessment of roses of the floribunda group (Floribunda) from the collection of the Central Botanical Garden of the National Academy of Sciences of Belarus - Nikonovich Tatiana Ivanovna (Hortus Botanicus)
Morphometric descriptions of 22 varieties of roses of the floribunda group from the collection of the Central Botanical Garden of the National Academy of Sciences of Belarus have been carried out. The height and shape of the bush, the color of the foliage and flowers, the size and shape of the flowers, the number of flowers in the inflorescence are determined. The winter hardiness of plants, resistance to diseases and adverse environmental factors were evaluated.